Absorber layer improvement and performance analysis of CIGS thin-film solar cell - A., Khamis; N. I. M., Rodzi; Noor Zirwatul Ahlam, Naharuddin (S.C. Virtual Company of Phisics S.R.L, 2024)
CIGS has shown significant potential for cost-effective and efficient photovoltaic applications, with efficiency often exceeding 20%. However, further improvements in cell performance are needed to reduce production costs. Thus, this study proposes an ultra-thin structure for CIGS solar cells by modifying the absorber layer thickness and composition. SCAPS software was used to evaluate the performance of the proposed design, such as open-circuit voltage (Voc), short-circuit current (Jsc), fill factor (FF%), and conversion efficiency (ŋ%). Results showed that ultra-thin solar cells with the proposed GnP and CGS absorber layers are ideal due to their greater ŋ%, 25.33%.